Inovação militar centrada em capacidades tecnológicas: o caso Type 094a da marinha do exército de libertação chinês - França, Iury Mendonça Freire de (2023)
In the context of a potential Soviet invasion in the 1980s, China's Central Military Commission approved a new strategic guideline known simply as “Active Defense”. This consists of using proactive offensive actions to defend against enemy attack. In 2015, the strategic notion of Active Defense, a pillar for the Navy's expanding operations, was updated for more distant waters. This paper aims to analyze how a military innovation case study of China's submarine force contributes to the operationalization of the Active Defense strategy. The Type 094A case study becomes relevant in view of Chinese investments in military innovation, which produced a less noisy and more technologically equipped submarine model, a cornerstone in the country's new maritime doctrine and a maritime component of the Chinese nuclear triad. Using the congruence method, a manifestation of the military innovation phenomenon is analyzed in the Type 094A case. The time frame starts from the submarine launch (2016) until the publication of this research. By traversing the geopolitical environment and Chinese maritime doctrine through the lens of military innovation, the research reveals how the shift in posture from Active Defense to power projection in distant seas has driven China's military development. We conclude that the research looked at incremental innovation, also understood as modernization. With its stealth and deterrence capabilities, the Type 094A strengthens the claim to operate in waters farther from China's coast and reduces the risks to do so.